Hallmarks of cancer: The insulin-like growth factors perspective - Werner, Haim; LeRoith, Derek (Frontiers in Oncology, 2022)
The identification of a series of attributes or hallmarks that are shared by virtually all cancer cells constitutes a true milestone in cancer research. The conceptualization of a catalogue of common genetic, molecular, biochemical and cellular events under a unifying Hallmarks of Cancer idea had a major impact in oncology. Furthermore, the fact that different types of cancer, ranging from pediatric tumors and leukemias to adult epithelial cancers, share a large number of fundamental traits reflects the universal nature of the biological events involved in oncogenesis. The dissection of a complex disease like cancer into a finite directory of hallmarks is of major basic and translational relevance. The role of insulin-like growth factor-1 (IGF1) as a progression/survival factor required for normal cell cycle transition has been firmly established. Similarly well characterized are the biochemical and cellular activities of IGF1 and IGF2 in the chain of events leading from a phenotypically normal cell to a diseased one harboring neoplastic traits, including growth factor independence, loss of cell-cell contact inhibition, chromosomal abnormalities, accumulation of mutations, activation of oncogenes, etc. The purpose of the present review is to provide an in-depth evaluation of the biology of IGF1 at the light of paradigms that emerge from analysis of cancer hallmarks. Given the fact that the IGF1 axis emerged in recent years as a promising therapeutic target, we believe that a careful exploration of this signaling system might be of critical importance on our ability to design and optimize cancer therapies.